1995
DOI: 10.1017/s0890037x0002340x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Rainfree Period After Asulam Application on Johnsongrass (Sorghum halepense)Control

Abstract: A rainfall simulator was used to deliver the equivalent of 1.3 cm of water in 0.25 h at 0, 3, 6, 12, 24, and 48 h after POST applications of asulam to johnsongrass in greenhouse and field studies. Johnsongrass control responses were similar when asulam was applied with either a crop oil concentrate or a commercially blended organosilicone/crop oil concentrate premix. Rainfall 24 h after asulam application reduced johnsongrass control in greenhouse studies. Maximum visual johnsongrass control of 80, 69, and 69%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…c A non-ionic surfactant (0.25% v/v) was added to all herbicide treatments. -------------g/ha ----------------------------------------------------------------------g ---------------------------------------------------- This result might be partially explained by the slow activity of asulam (Bruff et al 1995;Millhollon 1976;Richard 1986Richard , 1990. At 4 WAT, the effects of asulam on johnsongrass were incomplete.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…c A non-ionic surfactant (0.25% v/v) was added to all herbicide treatments. -------------g/ha ----------------------------------------------------------------------g ---------------------------------------------------- This result might be partially explained by the slow activity of asulam (Bruff et al 1995;Millhollon 1976;Richard 1986Richard , 1990. At 4 WAT, the effects of asulam on johnsongrass were incomplete.…”
Section: Resultsmentioning
confidence: 94%
“…Asulam fails to completely control rhizome johnsongrass. Asulam also requires an extended rain-free period for maximum control (Bruff et al 1995;Richard 1986). Failure to control johnsongrass results in higher infestation levels in subsequent ratoon crops, warranting the premature destruction of the crop to rehabilitate fields.…”
mentioning
confidence: 99%
“…Most simulated rainfall studies to investigate the potential of adjuvants to enhance herbicide efficacy and rainfastness have been conducted in the greenhouse. Weed response to simulated rainfall in the field may differ from the greenhouse, as observed with asulam on johnsongrass (Bruff et al 1995). This research evaluated the effect of various adjuvants with glyphosate on rainfastness and johnsongrass control under field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The longer time was required in the field study due to a slight rainfall around 3 h after asulam application. Bruff et al (1995) reported that rhizomatous johnsongrass control of 80, 69 and 69% was obtained in field studies when rainfall occurred 20, 14 and 8 h after asulam application, respectively. It was also assumed that asulam activities were slow in controlling the weed due to lower temperature (Hoagland 1996; Guttieri & Eberlein 1997; Tapia et al 1997).…”
Section: Resultsmentioning
confidence: 99%